Previous Gestational Diabetes Mellitus and Markers of Cardiovascular Risk - Nikolaos Vrachnis; Areti Augoulea; Zoe Iliodromiti; Irene Lambrinoudaki; Stavros Sifakis; George Creatsas (International Journal of Endocrinology)
The prevalence of gestational diabetes mellitus (GDM) in the developed world has increased at an alarming rate over the last few decades. GDM has been shown to be associated with postpartum diabetes, insulin resistance, hypertension, and dyslipidemia. A history of previous GDM (pGDM), associated or not with any of these metabolic abnormalities, can increase the risk of developing not only type 2 diabetes mellitus but also cardiovascular disease (CVD) independent of a diagnosis of type 2 diabetes later in life. In this paper we discuss the relationship among inflammatory markers, metabolic abnormalities, and vascular dysfunction in women with pGDM. We also review the current knowledge on metabolic modifications occurring in normal pregnancy and the link between alterations of a normal metabolic state with the long-term maternal complications that may result in increased CVD risk. Our review of studies on pGDM prompts us to recommend that these women be considered a population at risk for later CVD events, which however could be avoided via the use of specially designed follow-up programs in the future.